More than seizures: improving the lives of people with refractory epilepsy. (4th November 2014) - Mula, M.; Cock, H. R.
<x xml:space="preserve">Abstract</x> As captured by the proposed new definition, epilepsy is increasingly recognized as a disorder characterized not only by an enduring predisposition to recurrent seizures but explicitly also by the neurobiological, cognitive, psychological and social consequences of this condition. Further, both in the estimated 15 million people worldwide who have ongoing seizures despite optimal management and in a substantial proportion of those in remission, the consequences and comorbidities of epilepsy are the major determinants of quality of life. These include mood disorders such as anxiety and depression, dose related and longer term effects of antiepileptic drugs, including on prenatal development and bone health, and neurobehavioural effects. Whilst separating those that are part of an underlying condition or have unrelated contributors from those that are potentially remediable can be difficult, given the range of tools now available to assist with screening and management there is no excuse for not at least trying as part of standard care for people with epilepsy. Managing epilepsy well is about much more than controlling seizures and this needs to be recognized in planning and delivering services, as well as in prioritizing research.